Pretending is lying - Goblet, Dominique; Yanow, Sophie, 1987- (New York : New York Review Comics, 2016)
"Pretending Is Lying is a memoir unlike any other. The first book to appear in English by the acclaimed Belgian artist Dominique Goblet, it is at once an intimate account of love and familial dysfunction and an audacious experiment in graphic storytelling. In a series of dazzling fragments--skipping through time, and from raw, slashing color to delicate black and white--Goblet examines the most important relationships in her life: with her partner, Guy-Marc; with her daughter, Nikita; with her alcoholic, well-meaning father; and with her abusive mother. More than a decade in the making, the result is an unnerving comedy of paternal dysfunction, an achingly ambivalent love story (with asides on the Beach Boys), and a searing account of childhood trauma--a dizzying, unforgettable view of a life in progress and a tour de force of the art of comics"--
boek
Keywords: Goblet, Dominique; Cartoonists -- Belgium -- Biography -- Comic books, strips, etc